Penerapan Metode Qiro'ati Untuk Meningkatkan Minat Anak Dalam Belajar Al-Qur'an di TPQ Jam'iyatul Qurra', Banyuanyar, Probolinggo - Indiarti, Kinanti (Lembaga Penelitian, Penerbitan, dan Pengabdian Masyarakat, 2024)
Focuses on the importance of Al-Qur'an education as a basis for forming children's moral and intellectual character, as well as the challenges faced by the Al-Qur'an Education Park (TPQ) in maintaining children's interest in religious studies amidst the influence of the modern world and urbanization. This research aims to increase interest and skills in reading the Al-Qur'an at TPQ Jam'iyatul Qurra', Banyuanyar, Probolinggo, through the application of the Qiro'ati method. This method has proven to be effective in teaching reading the Koran correctly and creating a pleasant learning experience for students. The research was carried out using a community service approach, involving children aged 2 to 7 years and over. The results show a significant increase in understanding and skills in Al-Qur'an tartil, as well as motivating parents to be more active in enrolling their children in TPQ. The application of this method also supports the memorization of the letters of the Qur'an, making it a strategy that has the potential to be applied in other educational institutions to increase interest in learning the Qur'an on an ongoing basis.